High-performance ultraviolet-visible driven ZnO morphologies photocatalyst obtained by microwave-assisted hydrothermal method - Byzynski, Gabriela [UNESP] (2018)
The use of extensive, time-consuming synthesis and the cost of an additional element in synthesis makes difficult the synthesis of photocatalyst active under a broad wavelength range. We propose a synthesis method to obtain ZnO nanoparticles in distinctive morphologies, which lie to several photocatalytic activation conditions. The Zn precursor concentration, solvent, temperature and reaction time altered the ZnO particles morphologies. Although all synthesis parameters modification interferes in ZnO particle morphology, the most pronounced was Zn salt precursor concentration. The synthesis parameter did not interfere in the crystalline wurtzite ZnO phase and the optical characterization, indicating possibilities of ionic defects formations in ZnO lattice. The “3-D flower like” ZnO structure reaches 98% of discoloration under UV illumination and 42% under visible illumination of initial rhodamine-B concentration. The good UV and visible photocatalytic active confirms that with only the modification of synthesis method without any dopant element, ZnO structure is active in large wavelength range.